199. Short versus Extended Antibiotic Treatment with a Carbapenem for High-risk Febrile Neutropenia in Hematology Patients with Fever of Unknown Origin: A Randomized Multicenter Noninferiority Trial. (31st December 2020) - de Jonge, Nick A; Sikkens, Jonne; Zweegman, Sonja; Beeker, Aart; Ypma, Paula; Herbers, Alexandra; Vasmel, Wies; de Kreuk, Arne; Coenen, Juleon; Lissenberg-Witte, Birgit; Budding, Andries; Kramer, Mark; et al.
Abstract: Background: In hematology patients with high risk neutropenia due to intensive chemotherapy the optimal antibiotic treatment duration for fever of unknown origin (FUO) is unknown. Early antibiotic discontinuation has been advocated to reduce unnecessary exposure to broad-spectrum antibiotics, but there is limited evidence for the safety of this strategy. We aimed to assess if short treatment with carbapenems is non-inferior to extended treatment for neutropenic patients with FUO. Methods: Multicenter, open-label, randomized clinical trial in 6 centers in the Netherlands. Hematology patients with FUO during high risk neutropenia (≥7 days) were eligible for participation. Eligible patients who gave informed consent were randomly assigned (1:1) to either the short treatment arm, where the carbapenem was discontinued after 72 hours, irrespective of presence of fever, or the extended treatment arm, where the carbapenem was continued for ≥ 9 days until afebrile for 5 days or end of neutropenia (EON), whichever came first. The primary endpoint was treatment failure defined as a composite of recurrent fever or a carbapenem-sensitive infection between day 4 and day 8 and septic shock or death from day 4 until EON. Secondary endpoints included all-cause and infection-related mortality until 30 days post-EON. We used 10% as noninferiority margin. Trial Intervention Flowchart Results: Between December 2014 and August 2019 292 patients were included. Risk of treatment failure in the modified intention-to-treat analysis (mITT) was 23.5% (32/136) in the short treatment versus 18.3% (24/131) in the extended treatment arm (adjusted risk difference (ARD) 3.7% (90% CI -2.6% to 9.9%)) and in the per-protocol analysis 27.9% (29/104) versus 18.2% (22/121) (ARD 8.9% (90% CI 0.6% to 17.2%). Short treatment was non-inferior to extended treatment in the mITT population, but not in the per protocol population. All-cause mortality until 30 days post-EON was significantly higher in the short treatment group: 3.7% (5/136) versus 0.8% (1/131) (ARD 2.8%, 95% CI 1.3 to 4.4%), but infection-related mortality until 30 days post-EON was not statistically different between the treatment arms. Primary and Secondary Endpoint Results Subgroup Analyses Results Bloodstream infections after day 3 Conclusion: Short treatment with a carbapenem in neutropenic patients with fever was noninferior to extended treatment with regard to treatment failure. Conclusion Summary Disclosures: All Authors : No reported disclosures